Atmospheric atomic layer deposition of SnO2 thin films with tin(ii) acetylacetonate and water. Issue 24 (7th June 2022) - Nguyen, Viet Huong; Akbari, Masoud; Sekkat, Abderrahime; Ta, Huong T. T.; Resende, Joao; Jiménez, Carmen; Musselman, Kevin P.; Muñoz-Rojas, David
Abstract : Our work presents a new process for the spatial atomic layer deposition (SALD) of SnO2 thin films from tin(ii ) acetylacetonate and water, supported by a DFT study of different Sn metalorganic precursors. Abstract : Due to its unique optical, electrical, and chemical properties, tin dioxide (SnO2 ) thin films attract enormous attention as a potential material for gas sensors, catalysis, low-emissivity coatings for smart windows, transparent electrodes for low-cost solar cells, etc . However, the low-cost and high-throughput fabrication of SnO2 thin films without producing corrosive or toxic by-products remains challenging. One appealing deposition technique, particularly well-adapted to films presenting nanometric thickness is atomic layer deposition (ALD). In this work, several metalorganic tin-based complexes, namely, tin(iv ) tert -butoxide, bis[bis(trimethylsilyl)amino] tin(ii ), dibutyltin diacetate, tin(ii ) acetylacetonate, tetrakis(dimethylamino) tin(iv ), and dibutyltin bis(acetylacetonate), were explored thanks to DFT calculations. Our theoretical calculations suggest that the three last precursors are very appealing for ALD of SnO2 thin films. The potential use of these precursors for atmospheric-pressure spatial atomic layer deposition (AP-SALD) is also discussed. For the first time, we experimentally demonstrate the AP-SALD growth of SnO2 thin films using tin(ii ) acetylacetonate (Sn(acac)2 ) and water. We observe that Sn(acac)2 exhibits efficient ALD activity with a relatively large ALD temperature window (140–200 °C), resulting in a growth rate of 0.85 ± 0.03 Å per cyc. XPS analyses show a single Sn 3d5/2 characteristic peak for Sn 4+ at 486.8 ± 0.3 eV, indicating that a pure SnO2 phase is obtained within the ALD temperature window. The as-deposited SnO2 thin films are in all cases amorphous, and film conductivity increases with the deposition temperature. Hall effect measurements confirm the n-type nature of SnO2 with a free electron density of about 8 × 10 19 cm −3, electron mobility up to 11.2 cm 2 V −1 s −1, and resistivity of 7 × 10 −3 Ω cm for samples deposited at 270 °C.